Pirra Jungku: Comparison of traditional and contemporary fire practices on Karajarri Country, Western Australia. (28th January 2022) - Blackwood, Edward M. J.; Rangers, Karajarri; Bayley, Sam; Bijlani, Hamsini; Fensham, Rod J; Lindsay, Malcolm; Noakes, Ewan; Wemyss, Jackie; Legge, Sarah
Summary: Traditional fire practices in Australia's deserts may have created mosaics of post‐fire seral stages that benefitted some plants and animals. Managing fire to emulate the patterns produced by traditional burning practices is a common objective in contemporary conservation planning in Australia's deserts. However, the extent to which traditional burning in deserts affected fire regimes across space and time is contested. We aim to contribute to knowledge about the impacts of traditional burning on fire patterns in the Great Sandy Desert, northwest Australia. Our study covered the traditional lands of the Karajarri people, where some families were living a traditional lifestyle on Country until the 1960s. We analysed high‐quality aerial photographs taken over 18, 000 km 2 of Karajarri Country in the 1940s. Fire footprints up to several years old were mapped from these images, and their spatial characteristics were compared to those of contemporary fire regimes over the same area, visualised using high‐resolution Sentinel satellite imagery. Fires in the 1940s (considered traditional) were more numerous but much smaller than contemporary (2016–2020) fires. The areal extent of recently burnt areas was smaller and the fire frequency was lower in the 1940s. Contemporary fire patterns around cultural sites differed little from fire patterns elsewhere in the landscape, possibly because people were burning over large areas rather than only at localised sites. Our study suggests that Karajarri influenced fire patterns at a landscape scale in the Great Sandy Desert, at least during periods of average rainfall. The findings are helping Karajarri refine fire management goals, for example, by informing the size and dispersion of future burns, and supporting community discussion about fire and culture. Fire management outcomes for plants and animals are being tracked with a biodiversity monitoring program.